Building a Generation of Qualified Leaders: Leadership Education Strategies in Schools - Anang Sugeng Cahyono; Laros Tuhuteru; Sinta Julina; Suherlan Suherlan; Abu Muna Almaududi Ausat (Departement of Mathematics Education, 2023)
Indonesia needs leaders who are able to face complex challenges in various fields, such as political, economic, social, and environmental. However, the quality of leaders in Indonesia is still far from expectations, especially in terms of integrity, effective leadership, and the ability to tackle complex problems. Education is one of the important factors in shaping the generation of qualified leaders. This study aims to analyse leadership education strategies in schools that are effective in shaping a generation of quality leaders. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The results of this study reveal that leadership education in schools is an important strategy in building a generation of qualified leaders. To achieve this goal, a comprehensive and integrated programme is needed in the school curriculum such as instilling leadership values early on, providing leadership training to students, creating mentoring and self-development programmes, and encouraging students to be involved in leadership activities at school. Teachers and school staff should have the knowledge and skills in guiding students in developing their leadership abilities.